Transjugular portal vein recanalization with creation of intrahepatic portosystemic shunt (PVR-TIPS) in patients with chronic non-cirrhotic, non-malignant portal vein thrombosis - Klinger, Christoph; Riecken, Bettina; Schmidt, Arthur; De Gottardi, Andrea; Meier, Benjamin; Bosch, Jaime; Caca, Karel (Zeitschrift für Gastroenterologie, 2018)
Purpose To determine safety and efficacy of transjugular portal vein recanalization with creation of intrahepatic portosystemic shunt (PVR-TIPS) in patients with chronic non-cirrhotic, non-malignant portal vein thrombosis (PVT).Methods This retrospective study includes 17 consecutive patients with chronic non-cirrhotic PVT (cavernous transformation n = 15). PVR-TIPS was indicated because of variceal bleeding (n = 13), refractory ascites (n = 2), portal biliopathy with recurrent cholangitis (n = 1), or abdominal pain (n = 1). Treatment consisted of a combination of transjugular balloon angioplasty, mechanical thrombectomy, and—depending on extent of residual thrombosis—transjugular intrahepatic portosystemic shunt and additional stenting of the portal venous system.Results Recanalization was successful in 76.5 % of patients despite cavernous transformation in 88.2 %. Both 1- and 2-year secondary PV and TIPS patency rates were 69.5 %. Procedure-related bleeding complications occurred in 2 patients (intraperitoneal bleeding due to capsule perforation, n = 1; liver hematoma, n = 1) and resolved spontaneously. However, 1 patient died due to subsequent nosocomial pneumonia. During follow-up, 3 patients with TIPS occlusion and PVT recurrence experienced portal hypertensive complications.Conclusions PVR-TIPS is safe and effective in selected patients with chronic non-cirrhotic PVT. Due to technical complexity and possible complications, it should be performed only in specialized centers with high experience in TIPS procedures.
Keywords: portal vein thrombosis; transjugular intrahepatic portosystemic shunt; JAK2; portal hypertension; treatment; thrombectomy